Unobstructed Multiscale Imaging of Tissue Sections for Ultrastructural Pathology Analysis by Backscattered Electron Scanning Microscopy. (January 2020) - Reichelt, Mike; Sagolla, Meredith; Katakam, Anand K.; Webster, Joshua D.
Ultrastructural analysis of healthy, diseased, or experimental tissues is essential in diagnostic and investigative pathology. Evaluation of large tissue areas with suborganelle resolution is challenging because biological structures ranging from several millimeters to nanometers in size need to be identified and imaged while maintaining context over multiple scales. Imaging with field emission scanning electron microscopes (FE-SEMs) is uniquely suited for this task. We describe an efficient workflow for the preparation and unobstructed multiscale imaging of tissue sections with backscattered electron scanning electron microscopy (BSE-SEM) for applications in ultrastructural pathology. We demonstrate that a diverse range of tissues, processed by conventional electron microscopy protocols and avoiding the use of mordanting agents, can be imaged on standard glass slides over multiple scales, from the histological to the ultrastructural level, without any visual obstructions. Our workflow takes advantage of the very large scan fields possible with modern FE-SEMs that allow for the acquisition of wide-field overview images which can be explored at the ultrastructural level by digitally zooming into the images. Examples from applications in pulmonary research and neuropathology demonstrate the versatility and efficiency of this method. This BSE-SEM-based multiscale imaging procedure promises to substantially simplify and accelerate ultrastructural tissue analysis in pathology.